Analysis of e-learning implementation in adult learning (andragogy) - Indah Namira Sari; Dinn Wahyudin; R. Rusman (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
E-learning has relevance to be applied to adult learning as independent learners. This research aims to analyze the effectiveness of e-learning in adult learning (andragogy). In the context of adult learning based on continuous e-learning, there are significant changes in the objectives and content of teaching, social roles, forms, and nature of communication between teachers and students, based on e-learning. The research method uses a literature study of 77 articles found and analyzed based on the steps used. The research results showed that articles regarding e-learning in adult learning were found on the topics